COGNITIVE IMPAIRMENT AND ACTIVITY DAILY LIVING IN THE ELDERLY - Mohammad Andhika Setyawan; Dewi Hartinah; Ashri Maulida Rahmawati (Universitas Muhammadiyah Kudus, 2025)
Cognitive decline is common in the elderly, caused by natural brain aging and other factors such as lack of mental and social stimulation, and chronic diseases such as hypertension and diabetes. As a result, elderly people with cognitive impairment often experience decreased independence in daily living activities , quality of life, thus increasing the need for care and support from family and health workers . This research aims analyze the relationship cognitive impairment with activitiy daily living for the elderly in village A. The study used a cross-sectional method. The research sample of 62 respondents was selected through the Random Sampling technique. The activity daily living questionnaire used the Barthel Index and the cognitive impairment questionnaire used the Mini Mental State Exam (MMSE) which was valid and reliable. Data analysis used the Spearman Rank test. The results of the study showed Cognitive disorders in the elderly in Village A were mostly probable cognitive disorders, amounting to 28 respondents (45.2%). Daily living activities in the elderly are mostly dependent on 34 respondents (54.8%). There is a relationship between cognitive disorders and daily living activities in Village A because the p-value is 0.001 (a = 0.05) with a correlation coefficient value (0.443), meaning that the better the cognitive disorder, the lower the dependency on daily living activities.